[Rocky Shore of Lake Tekapo] - Streng, Evelyn Fiedler (1986)
Photograph of Lake Tekapo which is the second-largest of three roughly parallel lakes running north-south along the northern edge of the Mackenzie Basin in the South Island of New Zealand. It is fed at its northern end by both the braided Godley River and Macaulay River, which have their sources in the Southern Alps to the north. The meltwater from the Southern Alps is tinged with a light turquoise color from the glacial silt.